Exploring Team-Teaching Experiences of Preservice Teachers in Emergency Remote Teaching - Baylan, Steven L. (Academia Journal of Humanities & Social Sciences, 2026)
The abrupt shift to a digitally-only learning space in response to the global scourge of the COVID-19 pandemic triggered a myriad of challenges yet offered opportunities for Teacher Education Institutions (TEIs) to rethink assumptions about preservice teacher education (PTE). In particular, the education crisis has incited a growing interest in initiating a nonconventional approach to hands–on teaching practices for preservice teachers as a panacea for teacher preparation reform. This study, therefore, aims to unravel the experiences of preservice teachers (n=12) in team-teaching during their remote teaching internship using qualitative data collected through a qualitative research instrument. Employing a content analysis approach infused with inductive thematic analysis, the result captured the preservice teachers’ pedagogical praxis experiences, characterized by a nexus of the intertwining team accountability for teaching and learning space, collegial interactions, and promotive interdependence despite the remote teaching abyss presumed to be potential contextual barriers and impediments to the teaming. An implication for teaching internship mentors to craft teaching interns’ Learning Support Module (TILSM) to enhance preservice teachers’ teaming and digital literacy and fluency is put forward. The findings contribute to a novel aspect of team-teaching by providing insights into the potential benefits of team-teaching for preservice teachers in a remote teaching context.